The effect of a prior short-term ageing on mechanical and creep properties of P92 steel - Sklenicka, V.; Kucharova, K.; Svobodova, M.; Kral, P.; Kvapilova, M.; Dvorak, J. (Materials characterization, 2018)
We have investigated the effect of prior short-term ageing on the mechanical and creep properties of tungsten and boron modified 9%Cr ferritic steel (ASTM Grade P92 steel), to provide material data base for the estimation of material degradation due to occurrence of accidental overheating in the early stage of service loading. The steel was aged at 650°C for up to 100, 200, 500, 1000, 2000 and 5000h prior to mechanical and creep testing. Changes in the microstructure during ageing had a slight effect on the reduction of room temperature tensile properties. A sudden decrease on impact properties occurred after ageing for 2000h, but the occurred impact energy of about 70J is in accordance with the specified minimum value of 68J at room temperature for the virgin condition. The creep behaviour of P92 steel in the as-received condition and after different isothermal ageing exposures prior to creep was investigated at 600 and 650°C in the power-law creep regime. The initial applied tensile stress ranged from 90 to 200MPa. The results clearly show a detrimental influence of isothermal ageing on creep properties even after a few hundred hours. Based on microstructure analysis, which was done mostly in a qualitative way, a significant decrease in the creep life after ageing resulted from changes of the dislocation substructure and instability of Laves phase and M23C6 particles. •The results of simulated ageing at 650°C allows to estimate degradation of P92 steam pipes due to accidental overheating.•Simulated ageing has only a slight effect on ambient tensile properties and hardness.•A sudden decrease in impact properties occurred after ageing for 2000h. The FATT of about 25°C was determined.•The creep results show a clear detrimental influence of tempering ageing on the creep strength.•No Z-phase precipitation occurred due to the ageing process.